Mitochondrial DNA copy number is associated with all‐cause mortality and cardiovascular events in patients with peripheral arterial disease. (9th February 2020) - Koller, A.; Fazzini, F.; Lamina, C.; Rantner, B.; Kollerits, B.; Stadler, M.; Klein‐Weigel, P.; Fraedrich, G.; Kronenberg, F.
Abstract: Background: Dysfunctional mitochondria have an influence on inflammation and increased oxidative stress due to an excessive production of reactive oxygen species. The mitochondrial DNA copy number (mtDNA‐CN) is a potential biomarker for mitochondrial dysfunction and has been associated with various diseases. However, results were partially contrasting which might have been caused by methodological difficulties to quantify mtDNA‐CN. Objective: We aimed to investigate whether mtDNA‐CN is associated with peripheral arterial disease (PAD) as well as all‐cause mortality and cardiovascular events during seven years of follow‐up. Methods: A total of 236 male patients with PAD from the Cardiovascular Disease in Intermittent Claudication (CAVASIC) study were compared with 249 age‐ and diabetes‐matched controls. MtDNA‐CN was measured with a well‐standardized plasmid‐normalized quantitative PCR‐based assay determining the ratio between mtDNA‐CN and nuclear DNA. Results: Individuals in the lowest quartile of mtDNA‐CN had a twofold increased risk for PAD which, however, was no longer significant after adjusting for leukocytes and platelets. About 67 of the 236 patients had already experienced a cardiovascular event at baseline and those in the lowest mtDNA‐CN quartile had a 2.34‐fold increased risk for these events (95% CI 1.08–5.13). During follow‐up, 37 PAD patients died and 66 patients experienced a cardiovascular event. Patients in the lowest mtDNA‐CN quartile had hazard ratios of 2.66 (95% CI 1.27–5.58) for all‐cause‐mortality and 1.82 (95% CI 1.02–3.27) for cardiovascular events compared with the combined quartile 2–4 (adjusted for age, smoking, CRP, diabetes, prevalent cardiovascular disease, leukocytes and platelets). Conclusion: This investigation supports the hypothesis of mitochondrial dysfunction in peripheral arterial disease and shows an association of low mtDNA‐CNs with all‐cause‐mortality and prevalent and incident cardiovascular disease in PAD patients with intermittent claudication. Abstract :